2020
DOI: 10.15625/1813-9663/36/2/14786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Effectiveness of Ensemble Classifiers When Detecting Fuzzers Attacks on the Unsw-Nb15 Dataset

Abstract: The UNSW-NB15 dataset was created by the Australian Cyber Security Centre in 2015 by using the IXIA tool to extract normal behaviors and modern attacks, it includes normal data and 9 types of attacks with 49 features. Previous research results show that the detection of Fuzzers attacks in this dataset gives the lowest classification quality. This paper analyzes and evaluates the performance of using known ensemble techniques such as Bagging, AdaBoost, Stacking, Decorate, Random Forest and Voting to detect FUZZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Fuzzers assault systems by flooding them with a lot of random data to break them and identify faults. It can locate security gaps in networks and operating systems as well as vulnerabilities in software and systems [39]. It has been demonstrated that deep neural networks (DNNs) are extremely sensitive to even small changes in their input data.…”
Section: ) Fuzzersmentioning
confidence: 99%
“…Fuzzers assault systems by flooding them with a lot of random data to break them and identify faults. It can locate security gaps in networks and operating systems as well as vulnerabilities in software and systems [39]. It has been demonstrated that deep neural networks (DNNs) are extremely sensitive to even small changes in their input data.…”
Section: ) Fuzzersmentioning
confidence: 99%
“…Experimental results demonstrate that Ada boost with Naive Bayes Tree (NBTree) has the best accuracy score of 98.65 percent. In [12] Hoang Ngoc Thanh and Tran Van Lang suggested a fuzzers detection system using the UNSW-NB15 dataset, to analyze and evaluate the experimental outcomes. Single classifiers such (J48 (DT), logistic (LR), Lib SVM (SVM), Naive Bayes (NB), Random Tree (RT), and ibk (KNN)) were used in bagging, Ada boost, stacking, random forest, and decorate ensemble techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Thanh and Lang [14] suggested a fuzzers detection system using the UNSW-NB15 dataset. The system use ensemble methods such as Bagging, Ada Boost, Stacking, Decorate, and Random Forest for fuzzers detection.…”
Section: Related Workmentioning
confidence: 99%